Numerical estimation of internal stress relieving in destructive test - Szymczyk, Elżbieta; Derewońko, Agnieszka; Sławiński, Grzegorz; Jachimowicz, Jerzy (Computer Assisted Methods in Engineering and Science, 2017)
The paper deals with the analysis of residual stress fields in the riveted joint and the estimation of the internal stress magnitude releasing by partial and complete removing of the rivet material. Stress relieving causes deformations around the rivet hole, which can be measured and compared to the deformation state before removal. Numerical FE simulations of the upsetting process are carried out to determine the residual stress and strain fields. The contact with friction is defined between the mating parts of the joint. Non-destructive testing methods are used in combination with numerical calculations.